Sonic the hedgehog (2018), volume 7 ebook All or nothing. - Flynn, Ian (Sonic the Hedgehog (2018), 2020)
It's all come down to this, but will Sonic be able to overcome the odds and emerge victorious? The world has completely fallen to the Metal Virus. Sonic the Hedgehog and his friends find themselves on Angel Island, the last safe place, launching a desperate plan with their old foe, Dr. Eggman, to defeat the Deadly Six and reclaim the Chaos Emeralds in a last-ditch effort to save the world. Collects Sonic the Hedgehog issues #25–29.